Land drainage and flood defence 1999 delegate information : Monday 17 May 1999 (Thomas Telford, 1999)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present. Proceedings of a conference held on 17 May 1999.